Comparison of the methane potential obtained by anaerobic codigestion of urban solid waste and lignocellulosic biomass - H. I. Romero; C. A. Vega; J. D. Zuma; F. F. Pesantez; A. G. Camacho; F. F. Redrovan (Energy Reports, 2020)
The purpose of this research was to compare the methane gas (CH4) obtained through the anaerobic co-digestion between bean rind (Vicia faba) and pea rind (Pisum sativum) and the solid residues of El Macho stream of the city of Machala. For this, three 250 ml glass bioreactors were used, with the following composition: Reactor A (bean / sediment); Reactor B (pea / sediment); and Reactor C (bean + vetch / sediment). All bioreactors had a ratio of 1.7 between the lignocellulosic biomass (peel of bean and pea) and the RSU (sediment). A gas chromatograph was used to determine the methane concentration in the biogas obtained in the bioreactors. For the storage of the biogas, propylene bags were used. It was determined that, in Reactor A, after two weeks of anaerobic digestion, a greater concentration of methane was produced, with 39.52~±~0.28%; compared to 10.71~±~0.16% produced in Reactor B; and 2.11~±~0.03% in Reactor C. A comparison analysis of means was performed, where the statistical significance (p-value <0.05) allows to conclude that the composition of the co-digested biomass does influence the production of methane gas.
Keywords: 330; Biogas; Methane; Organic sediment